Rearing in a Physically Enriched Environment Affects Shoaling and Stress Responses of Zebrafish (Danio rerio) Exposed to Novel Conditions - Valentina Gazzano; Martina Di Filippo; Rosario Licitra; Asahi Ogi; Baldassare Fronte; Maria Claudia Curadi; Angelo Gazzano (Veterinary Sciences)
The impact of enrichment on stress reduction in zebrafish (Danio rerio) exposed to a novel environment was assessed. Four control shoals (CTRL) and five treated shoals (TRT), each with eight fish, were observed; in TRT tanks, a PVC pipe was included (three-way tube, 11.7 × 4 cm) as enrichment for 90 days. Subsequently, fish were moved to a new tank for a shoaling test, and behavior was evaluated over periods of 0′–5′ and 5′–10′. Cortisol dissolved in water was measured before and after the test. No differences were found between the two groups in distance moved, swimming speed, or shoal acceleration. Both groups reduced interindividual distance in the second phase of the test (CTRL: t = 8.977, p ≤ 0.0001; TRT: t = 8.247, p ≤ 0.0001), though TRT fish maintained greater spacing (t = 2.292, p ≤ 0.05). TRT fish spent more time without contact during both phases (first: t = 2.645, p ≤ 0.05; second: t = 3.134, p ≤ 0.01), while CTRL fish reduced this time in the second phase (t = 2.991, p ≤ 0.05). Cortisol rose significantly in CTRL after the test (t = 2.452, p ≤ 0.05) but not in TRT fish. These results suggest that environmental enrichment mitigates stress, as seen by reduced cohesiveness and cortisol in TRT fish.